CHI '05 Extended Abstracts on Human Factors in Computing Systems 2005
DOI: 10.1145/1056808.1056960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating navigational surrogate formats with divergent browsing tasks

Abstract: Navigational surrogates are representations that stand for information resources within search engine result sets, e-commerce sites, and digital libraries. They also form the basis of personal collections of media, such as web pages. Our hypothesis is that the formats of individual surrogates and collections play an important role in how people use collections. We are particularly interested in processes of information discovery, in which ideas are iteratively reformulated in the context of working with inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Qualitative data gives insight into how the composition form promotes distributed creative cognition when students use composition to represent prior work collections in collaborative invention projects (Kerne et al, 2007b). In all of these studies, and others (Kerne et al, 2005), most participants have preferred the composition to linear text representations, and experienced composition as easier to use.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Qualitative data gives insight into how the composition form promotes distributed creative cognition when students use composition to represent prior work collections in collaborative invention projects (Kerne et al, 2007b). In all of these studies, and others (Kerne et al, 2005), most participants have preferred the composition to linear text representations, and experienced composition as easier to use.…”
Section: Resultsmentioning
confidence: 89%
“…Composition means, "The act of putting together or combining … as parts or elements of a whole" (Oxford English Dictionary, 1992). The present research builds on a prior laboratory study (Kerne et al, 2005), which showed that users subjectively experience composition as an easier-to-use representation for navigational collections.…”
Section: Representing Collections With Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…We utilized a previously developed collection of information resources that represent six areas of the psychology curriculum: clinical psychology, consciousness, biopsychology, learning, developmental psychology, and perception [22]. For each area, there were six to ten information resources, each representing a subtopic.…”
Section: Psychology Resources Collections (Source Format)mentioning
confidence: 99%
“…Most responses to search queries are represented in the form of lists of textual surrogates [14,32,35]. Yet, studies have shown that users prefer image and text surrogates and understand them more readily [10,20]. Further, image and text representations facilitate the formation of mental models [13].…”
Section: Introductionmentioning
confidence: 99%